OS DESAFIOS NA ESCOLARIZAÇÃO DE ADOLESCENTES EM CUMPRIMENTO DE MEDIDA SOCIOEDUCATIVA DE LIBERDADE ASSISTIDA - Juscislayne Bianca Tavares de Morais (Universidade Federal do Maranhão, 2019)
This qualitative and bibliographical study deals with the schooling of adolescents in compliance with the socioeducative measure of Assisted Living (LA). This measure exists since the Menorista Codes and its operationalization is directly related to the presence of the adolescent in the school environment. If, during the period of the Menorista conception, LA aimed at surveillance, with the promulgation of the ECA, it is directly related to the adolescent's follow-up from the Integral Protection Doctrine. However, studies show that the relationship between school and LA has been marked by contradictions, beginning with the difficulty of these young people to effect school attendance. Another challenge is not to remain in school associated with multifactorial conditions, where the most overlapping is the non-investment of governments in socioeducation. The universality of teaching and school permanence are the two major challenges of socioeducation that will be discussed in this theoretical construct, in order to unveil the role that the school has been playing in the face of Assisted Freedom.